Some thoughts on the making of Irish index numbers - Geary, R. C. (Statistical and Social Inquiry Society of Ireland, 1946)
Ireland now possesses a fairly full range of price and quantum index numbers which is not to say that they cannot be improved or their range extended. One of the prime objects of the present paper is, in fact, to invite this learned Society (which is better qualified than any other body in the country to do so) to discuss the principles and manner of computation of the new wholesale price index number, prior to its official promulgation, I should explain further that my object is not to discuss the economic trends indicated by these various series. The paper deals almost exclusively with certain methodological aspects of the construction of index numbers: it is hoped, however, that some of the figures quoted illustratively may be found to have an interest in themselves.
Read on Friday, 27th October, 1944
Keywords: Index construction; Price index; Volume index; Quantum index; Index numbers, Ireland; 314.15